Novoe v organizatsii i upravlenii razvitiem fizicheskoi kul'turyi i sporta v Chuvashskoi respublike - Krasnov, V. M. (Teorija i Praktika fiziceskoj Kul'tury, 2000)
For the first time in Russia the Ministry of physical culture and sport was created in Chuvashiya . The ministry of physical culture and sport of Chuvashiya is a republican agency of the Chuvash Republic executive authority. In interaction with other republican agencies of the executive authority and with agencies of local self-management it provides realization of state policy in the field of physical culture work, sport, tourism and sanatorium business. The decisions, which are accepted by the Ministry of physical culture and sport of Chuvashiya are obligatory for execution by other ministries and other republican agencies of the executive authority, and also enterprises, establishments and organizations located in territory of the Chuvash Republic.